HIGHER EFFICIENCY OF MAGNETIC AND ABRASIVE MACHINING OF MACHINE PARTS’ DISCONTINUOUS SURFACES - L. M. Akoulovich; L. E. Sergeev; E. A. Korzoune; V. E. Babich (Наука и техника)
The paper proposes an analytical model for topography of a magnetic field while making magnetic and abrasive machining of discontinuous surfaces. Topography analysis has made it possible to determine a rational configuration of an operational zone of electromagnetic system pole pieces while machining gear wheel.